Association between obesity and liver cancer from 2012 to 2023: Bibliometric analysis and global trends - Wang, Donghong; Ma, Zhibin (Medicine (Baltimore), 2024)
Incidence rates of liver cancer have increased worldwide in recent decades, making it a major public health problem globally. Obesity can be caused by multiple factors and promotes the development of liver cancer in many ways. Although the research on the association between obesity and liver cancer was previously explored, we first employed bibliometrics to analyze the current research status. From 2012 to 2023, the Web of Science Core Collection database was searched for studies regarding the association between obesity and liver cancer. To evaluate worldwide trends and research hotspots in this topic, bibliometric analysis tools such as VOSviewer, CiteSpace, and R Package were employed. Altogether 233 eligible publications, consisting of 167 articles and 66 reviews, were analyzed. The yearly number of publications and average citation numbers have increased over the last 11 years, particularly the last 6 years. The great majority of published articles on this topic originated from the United States (n = 89, 38.20%), followed by China (n = 60, 25.75%), and England (n = 23, 9.87%). In this subject's research, American scholars embodied considerable production, great prominence, and high academic influence. The most cited article was Yoshimoto, S et al of Japan Science and Technology Agency published in 2013 with a citation number of 1410. We apply bibliometric analysis for the first time in this field, expecting to help scholars efficiently and effectively retrieve the association between obesity and liver cancer.